Art in Sweden : leaving the empty cube : Contemporary Swedish art. - Engblom, Soren (Stockholm : Swedish Institute Stockholm, 2002)
Antonsson, Lotta ; Bärtas, Magnus ; Bigert & Bergström ; Billgren, Ernst ; Billgren, Ola ; Book, Max ; Cronqvist, Lena ; Dahlgren, Jacob ; Dawid ; Edefalk, Cecilia ; Edholm, Ann ; Ellberg, Carin ; Gedin, Andreas ; Gyllenhammar, Charlotte ; Hafström, Jan ; Hakansson, Henrik ; Hausswolff, Annika von ; Helmersson, Katrine ; Isaeus-Berlin, Meta ; Johansson, Bengt Olof ; Karlsson Rixon, Annica ; Kristensson, Anders ; Lindberg, Maria ; Lindström, Tuija ; Löfdahl, Eva ; Lundberg, Mikael ; Matz, Ebba ; Melin, Truls ; Miesenberger, Maria ; Nilsson, Lars ; Orfali, Ingrid ; Partos, Christian ; Rehnberg, Hakan ; Reich, Carina ; Rollof, Ulf ; Samuelson, Ulrik ; Scott, Johan ; Senneby, Annette ; Sjolund, Stig ; Smoliansky, Gunnar ; Strömholm, Christer ; Svenungsson, Jan ; Szyber, Bogdan ; Tottie, Sophie ; Wallin, Magnus ; Wickström, Martin ; Widoff, Anders ; Wikstrom, Elin ; Wolgers, Dan ; Wrange, Mans ; Wretman, Fredrik
Engels
boek
Keywords: Zweden